Antibiotic stewardship in the neonatal intensive care unit. Issue 6 (June 2019) - Chakkarapani, Aravanan Anbu; Russell, Alison Bedford
Abstract: Antibiotic stewardship (ABS) refers to the coordinated interventions to appropriately prescribe and administer the most pathogen-specific, narrow-spectrum antibiotic regimens, in the correct doses, for the appropriate duration, and continually evaluate prescriber and administration compliance. The main historical driver for ABS has been antibiotic resistance, which is fuelled by antibiotic therapy. Additionally, short and long term consequences of antibiotic therapy on the developing immune system have emerged as further specific hazards of antibiotic exposure in neonates. The implementation of an ABS program, can be through ward-focused, multidisciplinary, antimicrobial teams, with promotion of evidence-based antimicrobial prescribing guidelines. Nursing and medical leadership should promote a united, pan-unit culture of it being "everybody's job" to embed an ABS program, alongside robust infection prevention practices and active promotion of breastfeeding. This review article will discuss the drivers for antibiotic stewardship and strategies for implementation of antibiotic stewardship within neonatal units.